Diagnosis and management of secondary epipapillary retinoblastoma. Issue 10 (9th February 2017) - Fabian, Ido Didi; Puccinelli, Francesco; Gaillard, Marie-Claire; Beck-Popovic, Maja; Munier, Francis L
Abstract : Background: Reports on retinoblastoma relapse at the optic nerve head (ONH) are anecdotal and include only treatments by external beam radiotherapy (EBRT) or enucleation. We aimed to describe such cases, termed secondary epipapillary retinoblastoma, diagnosed and monitored with the assistance of hand-held spectral domain optical coherence tomography (HHSD-OCT) and treated with intraophthalmic artery chemotherapy (IAC) and/or intravitreous chemotherapy (IViC). Methods: A retrospective analysis of secondary epipapillary retinoblastoma cases treated conservatively. Results: Four males and two females were included, diagnosed with secondary epipapillary retinoblastoma at a median time of 8.6 months (mean 24.0) from initial retinoblastoma diagnosis. HHSD-OCT was used in all cases for accurate diagnosis; in 2/6, the epipapillary relapse was detected only by means of HHSD-OCT. Treatments for secondary epipapillary retinoblastoma included IAC and IViC (n=4), IAC alone (n=1) and IViC alone (n=1). HHSD-OCT demonstrated complete epipapillary tumour regression in all cases, achieved in a median time of 1.6 months (mean 1.8). The median time from secondary epipapillary retinoblastoma resolution to last visit was 29.2 months (mean 27.5). At last visit, all eyes were tumour-free and no cases of metastasis recorded. Conclusions: Cases of retinoblastoma relapse at the ONH show common clinical features and represent specific diagnostic and therapeutic challenge; hence, we propose to consider this condition as a subset of retinoblastoma, termed secondary epipapillary retinoblastoma. HHSD-OCT is an invaluable diagnostic tool in the initial diagnosis as well as in monitoring these lesions, and IAC and IViC are efficient modalities for this clinical scenario, obviating the need for EBRT or enucleation.